QUALITATIVE AND QUANTITATIVE ANALYSIS USING AERIAL PARTS FROM DOUBLE FLOWER VARIETY OF TABERNEMONTANA DIVARICATA - C. Kalaimagal; G. Umamaheswari (International Journal of Ayurveda and Pharma Research, 2015)
Qualitative and quantitative phytochemical analyses were done using aerial parts of double flower variety of Tabernaemontana divaricata. Qualitative phytochemical analysis was performed to identify the presence of various phytoconstituents with standard procedures. Total phenols, total flavonoids and total protein were determined by folin-ciocaltaeu method, aluminium chloride colorimetric method and Lowrys method. Phytochemical screening exhibits the occurrence of alkaloids, flavonoids, terpenoids, cardiac glycosides, saponins, tannins, carbohydrates and protein. In quantitative analysis, elevated level of phenols, flavonoids and protein were identified in leaves, flowers and stem. The present study concluded that Tabernaemontana divaricata plant has the ability to cure a variety of diseases with antioxidant capacity because of the presence of phytochemicals in it.